El rango de los Tratados sobre Derechos Humanos - Montoya Chávez, Victorhugo (2015)
An issue that has sparked heated debate over the years is undoubtedly the hierarchy of international treaties in the Peruvian legal system. the critical point is whether these treaties have Constitutional status. thus, the authors seek the answer based on the hierarchy of laws and how Human Rights Treaties are defined nowadays. Furthermore, they analyze the arguments defending their constitutional status in order to arrive to a firm conclusion that considers the globalization process that Law is going through.